Pain Characteristics and Demographics of Patients Attending a University-Affiliated Pain Clinic in Toronto, Ontario - Angela Mailis-Gagnon; Balaji Yegneswaran; SF Lakha; Keith Nicholson; Amanda J Steiman; Danny Ng; Marios Papagapiou; Margarita Umana; Tea Cohodarevic; Mateusz Zurowski (Pain Research and Management)
BACKGROUND: Pain clinics tend to see more complex chronic pain patients than primary care settings, but the types of patients seen may differ among practices.